Comparison of the non-invasive Nexfin® monitor with conventional methods for the measurement of arterial blood pressure in moderate risk orthopaedic surgery patients. (August 2016) - Balzer, Felix; Habicher, Marit; Sander, Michael; Sterr, Julian; Scholz, Stephanie; Feldheiser, Aarne; Müller, Michael; Perka, Carsten; Treskatsch, Sascha
Objective: Continuous invasive arterial blood pressure (IBP) monitoring remains the gold standard for BP measurement, but traditional oscillometric non-invasive intermittent pressure (NIBP) measurement is used in most low-to-moderate risk procedures. This study compared non-invasive continuous arterial BP measurement using a Nexfin® monitor with NIBP and IBP monitors. Methods: This was a single-centre, prospective, pilot study in patients scheduled for elective orthopaedic surgery. Systolic BP, diastolic BP and mean arterial blood pressure (MAP) were measured by Nexfin®, IBP and NIBP at five intraoperative time-points. Pearson correlation coefficients, Bland–Altman plots and trending ability of Nexfin® measurements were used as criteria for success in the investigation of measurement reliability. Results: A total of 20 patients were enrolled in the study. For MAP, there was a sufficient correlation between IBP/Nexfin® (Pearson = 0.75), which was better than the correlation between IBP/NIBP (Pearson = 0.70). Bland–Altman analysis of the data showed that compared with IBP, there was a higher percentage error for MAPNIBP (30%) compared with MAPNexfin ® (27%). Nexfin® and NIBP underestimated systolic BP; NIBP also underestimated diastolic BP and MAP. Trending ability for MAPNexfin ® and MAPNIBP were comparable to IBP. Conclusion: Non-invasive BP measurement with Nexfin® was comparable with IBP and tended to be more precise than NIBP.